Чинники формування колекторських властивостей низькопористих теригенних порід. Стаття 1. Вплив розміру фільтрувальних каналів на проникність низькопористих теригенних порід - Лукінов, В.; Безручко, К. (Геологія і геохімія горючих копалин, 2009)
Показано схожість емпіричних формул, що характеризують залежність залишкової водонасиченості та відкритої пористості пісковиків Донбасу і Дніпровсько-Донецької западини. Відносна вологість у міру збільшення ступеня постдіагенетичних змін пісковиків зростає через підвищення вмісту зв.язаної вологи. За низьких коефіцієнтів відкритої пористості (< 4,4 %) велика частина порового простору (> 50 %) зайнята зв'язаною вологою. Проаналізовано вплив на її вміст розміру породотворних зерен, коефіцієнта сортування, вмісту глинистих мінералів. За цими показниками розбіжність пісковиків середнього та пізнього катагенезу незначна, натомість розбіжність ступеня заповнення пор вологою значна: 26 % - у зоні середнього катагенезу; 68,6 % - у зоні пізнього катагенезу. Аналітично досліджено вплив внутрішньої питомої поверхні порід на залишкову водонасиченість. Зроблено висновок, що питома поверхня порід (пісковиків, алевролітів) під час постдіагенетичних перетворень має зменшуватися із зниженням пористості, а розмір основних фільтрувальних каналів є головним чинником, який визначає абсолютну проникність низькопористих теригенних порід. Його необхідно використовувати для визначення проникності гірських порід. Similitude of empiric formulas which characterize dependence of residual water saturation and opened porosity of Donbas and Dnieper-Donets Depression sandstones is shown. It is shown that the relative humidity increase of sandstones with the increase of postdiagenetic degree changes occurs due to the increase of the bounded moisture content. At the low coefficients of opened porosity (< 4.4 %), a greater part of pore space (> 50 %) is occupied by bounded moisture. Influence of clay minerals content, sizes of rocks grains and coefficient of sorting on bounded moisture content is analyzed. Distinction of middle and late catagenesis sandstones by these indices is insignificant. On the contrary, distinction of a degree of pore moisture filling is considerable. 26 % in the middle catagenesis zone, 68.6 % - in the late catagenezis zone. Influence of rocks of internal specific surface on residual water saturation has been analytically investigated. A conclusion has been done, that the internal specific surface of rocks (sandstones, aleurolites) during postdiagenetic transformations must decrease with the reducing of porosity. Data are cited that pore space of Donbas sandstones was formed by pores of 10^-6 - 10^-8 m in size. Part of pores of 10^-7 m in size and less, is about 50 %. That is to say, a part of capillary moisture is considerable and its role in forming of residual water saturation too. The value of residual water saturation is determined by the size of pore channels. It leads to increase of the residual water saturation with decrease of porosity. Reduction of pore space occurs due to diminution of pores size. The conclusion has been done that the size of the basic filter channels is a fundamental factor which determines absolute permeability of low porous terrigenous rocks. Exactly the size of the filter channels must be used for determination of rocks permeability.